Objective measures of unobstructed walking and obstacle avoidance in Parkinson's disease subtypes - Orcioli-Silva, Diego [UNESP]; Vitorio, Rodrigo [UNESP]; Lirani-Silva, Ellen [UNESP]; Rocha Santos, Paulo Cezar [UNESP]; Beretta, Victor Spiandor [UNESP]; Bucken Gobbi, Lilian Teresa [UNESP] (Elsevier B.V., 2018)
Background: Objective measures of gait in Parkinson's disease (PD) patients according to motor subtypes are not yet fully understood. Although recent advances have been made for unobstructed walking, further work is required on locomotor tasks challenging postural stability, such as obstacle avoidance. Research question: This study aimed to investigate the influence of PD motor subtypes on objective measures of locomotion during unobstructed walking and obstacle avoidance. Methods: Thirty-five PD patients classified as postural instability and gait disorder (PIGD) and 30 as tremor dominant (TD), as well as 45 healthy controls (CG) walked along an 8-m pathway under two conditions: (a) unobstructed walking and (b) obstacle avoidance. Outcome measures included spatiotemporal parameters recorded by an optoelectronic tridimensional system. Results: During unobstructed walking, the PIGD group exhibited shorter stride length, slower velocity, and longer double support phase compared to the TD and CG groups. The TD group also presented slower stride velocity compared to the CG. The PIGD and TD groups presented shorter stride duration than the CG. Regarding obstacle avoidance, the PIGD group exhibited shorter distances for leading foot placement before obstacle, trailing foot placement after obstacle and trailing crossing step length compared to the TD and CG groups. The PIGD group exhibited wider leading crossing step width, lower trailing toe clearance, and slower leading and trailing velocity during obstacle avoidance compared to the CG. Significance: PIGD subtype patients showed worse modifications in objective measures of unobstructed walking and obstacle avoidance. The observed modifications may contribute to increased fall occurrence in PIGD patients.
Keywords: Gait; Obstacle avoidance; Parkinson's disease; PIGD; Tremor dominant